The mediating role of behavioral control on the intention to repurchase halal cosmetics - MANSUR CHADI MURSID; Andita Dwi Palupiningtyas; Abdul Hamid; Aenurofik Aenurofik (Jurnal MANAJERIAL, 2022)
The more growth in the cosmetic industry today does not rule out that there are cheats that occur either from the ingredients used or the chemical content contained in cosmetics. In the marketing world there is a theory about consumer behavior in choosing and consuming a product, namely Theory of Planned Behavior (TPB). TPB identifies influences that predict and change behavior, where behavioral intention is influenced by: a person's attitude, beliefs about whether an individual who is important to that person approves or disapproves of the behavior, and perceived control over performing the behavior. The purpose of this study was to determine the effect of consumer attitudes and subjective norms on the intention to repurchase halal cosmetics mediated by behavioral control on as many as 150 college students in Pekalongan with the sampling technique using purposive sampling. The analysis technique used in this research is the Structural Equation Modeling analysis technique with the help of the AMOS version 22 program. This research includes field research with a quantitative approach. Sources of data obtained from primary data and secondary data, while the data in this study were obtained from observations, questionnaires and documentation. Based on the results of the analysis in this study, the results show that (1) consumer attitudes have a positive and significant effect on behavior control, (2) subjective norms have a positive and significant effect on behavior control, (3) consumer attitudes have a positive and significant effect on repurchase interest, (4) subjective norm has a significant positive effect on the intention to repurchase cosmetic products labeled halal, (5) behavioral control has a positive and significant effect on repurchase interest, (6) Behavioral control can mediate the effect of consumer attitudes on consumer repurchase interest in halal cosmetic products , (7) Behavioral control can mediate the effect of subjective norms on consumer repurchase interest in halal cosmetic products.